2021
DOI: 10.1002/mp.15178
|View full text |Cite
|
Sign up to set email alerts
|

Combining computed tomography and biologically effective dose in radiomics and deep learning improves prediction of tumor response to robotic lung stereotactic body radiation therapy

Abstract: Purpose The aim of this study is to improve the performance of machine learning (ML) models in predicting response of non‐small cell lung cancer (NSCLC) to stereotactic body radiation therapy (SBRT) by integrating image features from pre‐treatment computed tomography (CT) with features from the biologically effective dose (BED) distribution. Materials and methods Image features, consisting of crafted radiomic features or machine‐learned features extracted using a convolutional neural network, were calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…It failed to achieve statistical significance due to the small sample size, subtle differences in the data set or the mixed effect of other parameters. Similar results were obtained by Avanzo et al who have demonstrated that combining BED features and image features in radiomics and deep learning improves the tumor response prediction of machine learning models for lung SBRT (42). This trend is in agreement with past studies, showing it is highly valuable to predict tumor local control in lung SBRT using multivariate factors (43).…”
Section: Discussionsupporting
confidence: 89%
“…It failed to achieve statistical significance due to the small sample size, subtle differences in the data set or the mixed effect of other parameters. Similar results were obtained by Avanzo et al who have demonstrated that combining BED features and image features in radiomics and deep learning improves the tumor response prediction of machine learning models for lung SBRT (42). This trend is in agreement with past studies, showing it is highly valuable to predict tumor local control in lung SBRT using multivariate factors (43).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, a 2021 study by Avanzo et al. found that the application of radiomics is of great value in improving lung stereotactic body radiation therapy ( 30 ). In clinical practice, radiomics is an emerging field of research, and it is used as a predictive tool for responses and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to chemotherapy and radiotherapy, targeted therapy, immunotherapy and combination therapy may provide more personalized and specialized options to improve patient survival. Furthermore, a 2021 study by Avanzo et al found that the application of radiomics is of great value in improving lung stereotactic body radiation therapy(30). In clinical practice, radiomics is an emerging field of research, and it is used as a predictive tool for responses and treatment outcomes.…”
mentioning
confidence: 99%
“…To alleviate this negative effect, we use several re-sampling techniques to balance the distribution in training cohort for model construction. The re-sampling techniques should be applied only to training data to avoid data leakage, while the validation cohort was untouched as it represents the real situation in clinical practice (24).Ten re-sampling techniques worked in our study: random over-sampling (ROS), Adaptive Synthetic (ADASYN), Synthetic Minority Oversampling Technique (SMOTE), Borderline SMOTE (bSMOTE), Random under-sampling (RUS), NearMiss (NM), Tomek links (TL), Edited Nearest Neighbours (ENN), Over-sampling using SMOTE and cleaning using Tomek links (SMOTE-TL) and Over-sampling using SMOTE and cleaning using ENN (SMOTE-ENN) (25)(26)(27). The re-sampling methods are described in the Supplementary Method S7.…”
Section: Re-sampling Methods For Unbalance Correctionmentioning
confidence: 99%